Analisis Permasalahan Pembelajaran Pendidikan Kewarganegaraan (PKn) Pada Siswa Madrasah Ibtidaiyah Negeri 8 Langkat - Ramadhani Lastari; Daulat Saragi (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The focus of this study is the problem of learning methods, learning resources, learning media and results. The values studied are the Civics scores of fifth grade students at MIN 8 Langkat taken from the report cards. This study aims to describe the Problems of Civics Learning and describe the results of Civics learning values for class V at MIN 8 Langkat. The research method used is descriptive qualitative with data collection techniques including observation, interviews and document studies. Based on the results obtained by researchers when they saw the learning situation in class IV that the learning methods used by the teacher were still not varied enough to make students often feel bored and even sleepy and for class V at MIN 8 Langkat entered at 13.00, so the teacher should have been more Pay attention to the learning methods used so that learning activities are more interesting. then learning resources only focus on textbooks (thematic books) or the teacher focuses too much on the material in the book. In addition, in the learning process the use of instructional media is still felt to be lacking and the results of student scores in Civics learning on average are still not appropriate even below the Minimum Completeness Criteria (KKM).